2014
DOI: 10.1111/are.12402
|View full text |Cite
|
Sign up to set email alerts
|

Spermiation time affect the milt quality indices of the Russian sturgeon,Acipenser gueldenstaedtii, Brandt & Ratzeburg, 1833

Abstract: In this study, the effects of spermiation time are investigated on milt quality of Russian sturgeon over the course of the spawning season. The milt samples were collected from three broodstock batches at three time points including: the beginning, middle and at the end of the spawning season. According to the results, the milt quality parameters including pH, sperm density, spermatocrit, duration of sperm motility and percentage of sperm motility were significantly low in the beginning and end of season than … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
2
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 19 publications
(15 reference statements)
1
2
2
Order By: Relevance
“…The mean of the total motility—TM% (74.4 ± 11.9) was similar to that recorded by Halimi et al [ 24 ] (69.6 ± 3.5%). The mean values of sperm mobility persistence of Russian sturgeon spermatozoa recorded in this study (2–4 min) were similar to those reported by Drabkina cit.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…The mean of the total motility—TM% (74.4 ± 11.9) was similar to that recorded by Halimi et al [ 24 ] (69.6 ± 3.5%). The mean values of sperm mobility persistence of Russian sturgeon spermatozoa recorded in this study (2–4 min) were similar to those reported by Drabkina cit.…”
Section: Discussionsupporting
confidence: 88%
“…The mean semen volume value collected from the Russian sturgeons was lower than that reported by Halimi et al [ 24 ], 86.3 ± 8.1 mL; however, it can be considered similar, given that in our study, one of the males (M2) gave out a smaller amount of semen during collection compared to the other males. A comparison of the results from the two studies reveals the possible influence of different factors on the volume of sperm collected: habitat (fish farm with recirculating aquaculture system versus southern part of the Caspian Sea), compounds used for spermiation induction (luteinizing hormone-releasing hormone agonists versus pituitary preparation PP) and other factors such as timing of sperm collection in relation to spawning period, handling techniques, restraint or anesthesia of males and method of sperm collection.…”
Section: Discussioncontrasting
confidence: 48%
See 1 more Smart Citation
“…In our study, sperm concentration was found lower than the studies carried out before (Halimi et al., ; Linhart et al.,). The lower sperm concentration seen in this study could be explained either this was the first stimulation of the fish used with hormone or the method used for evaluation of sperm concentration (Linhart et al., ; Piros et al., ; Rurangwa, Kime, Ollevier, & Nash, ).…”
Section: Introductioncontrasting
confidence: 89%
“…In some sturgeons species sperm can be collected without hormonal manipulation (Kopeika, Williot, & Goncharov, ; Toth, Ciereszko, Christ, & Dabrowski, ) while hormone injection leads to increase in volume of collected sperm (Brown & Mims, ; Gallis, Fedrigo, Jatteau, Bonpunt, & Billard, ; Halimi, Mohammadi, Norousta, Khara, & Karimi, ; Linhart et al., ; Tsvetkova, Cosson, Linhart, & Billard, ). Sperm volume for both hormone in this study was found higher in contrast of others studies (LHRH‐a 188 ± 91.91; CPP 151.33 ± 66.37).…”
Section: Introductionmentioning
confidence: 99%